Not all path is straight: limits and possibilities for the sensibilization of fashion design students through pattern making teaching - Pavei Souza, Bárbara; Cardoso Pereira, Adriana (Revista de Ensino em Artes, Moda e Design, 2020)
This paper aims at presenting a scope of pattern making teaching under the notions of Sensible Knowledge Pedagogy. Taking into consideration that the principle of current teaching methodologies are a reflection of the Cartesian Logics of the knowledge construction, the aim of the present study is to explore the limits and possibilities of the teaching and learning process of pattern making, aiming at encouraging the students of the area to establish various connections that might arouse from the dialogue between a garment and the human body. More specifically, it starts from the reports and concerns of the researchers as students and teachers of this course, as well as the bibliographic reference of this theme, attempted to trace an overview on the pattern making teaching as an experience, its relationships with the teaching and learning process and with the knowledge construction by the professionals of the Fashion Design College Degree. The study points to the remarkable presence of the instructional character of the teaching practices in regards to the tradicional pattern making, enhanced by methodologies and instructional materials that concentrate on the establishment orders and pre-determined models. Finally, some paths are outlined less rectilinear for the teaching and knowledge of this subject that can be confronted, in an educational context, not only as a step for the productive process, but also from the capability of building a territory within esthetic experimentation.